Factors Predicting Fear of Cancer Recurrence among Patients with Breast Cancer - Injai, Naraporn; Moungkum, Saifone; Masingboon, Khemaradee (Journal of The Royal Thai Army Nurses, 2021)
The fear of cancer recurrence is a psychological problem that makes patients with breast cancer have improper coping behaviors. This predictive correlational study aimed to evaluate the fear of cancer recurrence and its predictors in breast cancer patients receiving radiotherapy and/ or chemotherapy at the outpatient departments of Chonburi Cancer Hospital. Ninety-four patients with breast cancer were recruited by a simple random sampling method. The research instruments included the personal data record form, the Fear of Cancer Recurrence Inventory Short Form (FCRI-SF), the Brief Pain Inventory Short Form (BPI-T), the Thai version of 10-Item Perceived Stress Scale (T-PSS-10), the Life Orientation Test Revised (LOT-R) and, the Social Support Questionnaire (SSQ). The Cronbach alpha coefficients were .87, .92, .85, .84 and .98 respectively. Data were analyzed by descriptive statistics and multiple regression analysis. The results showed that 84 percent of the sample had a high level of fear of cancer recurrence (Mean = 22.80, SD = 5.76). Stress was only the factor that could predict fear of cancer recurrence among patients with breast cancer (β = .61, p <.05). Therefore, nurses should regularly assess the stress, causes of stress, and the fear of cancer recurrence in patients with breast cancer in order to promote patients’ ability to cope and manage stress properly to prevent fear of cancer recurrence during treatment.